A study of the scutellum in eight Chagas disease vector species from genus Triatoma (Hemiptera, Reduviidae) using optical and scanning electron microscopy - Obara, Marcos Takashi; Rosa, João Aristeu da [UNESP]; Ceretti Jr, Walter; Urbinatti, Paulo Roberto; Quintero, Lisardo Osório; Barata, José Maria Soares; Galvão, Cleber; Jurberg, José (Instituto Oswaldo Cruz, Ministério da Saúde, 2007)
The aim of this study was to analyze the external morphology of the scutellum through optical microscopy and scanning electron microscopy (SEM) in male specimens of Triatoma costalimai, T. delpontei, T. eratyrusiformis, T. matogrossensis, T. infestans melanosoma, T. sherlocki, T. tibiamaculata, and T. vandae. A total of 30 photographs of the scutellum were made. Magnification varied from 50X to 750X. Regarding depth and forms of the central depression, the heart-shaped form was predominant, with some exceptions, so that this shape appears to be a common characteristic for species of genus Triatoma Laporte, 1832. In T. eratyrusiformis, a kind of sensillum with important taxonomic value was observed. The different sizes and shapes of the designs found on the posterior process of the scutellum were also of important taxonomic interest. The study of the scutellum based on SEM showed valuable characteristics, allowing the use of this structure to aid the diagnosis of triatomine species. Thus, more specimens in subsequent studies and analyses of morphometric parameters should contribute to agreement on phylogenetic aspects in this genus. A Key to eight species of Triatoma based on male scutellar morphology is presented.
Keywords: scutellum; optical microscopy; scanning electron microscopy; Triatominae; Chagas disease